2022
DOI: 10.1088/1742-6596/2231/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

On a pseudo-periodicity in the elastodynamics

Abstract: The periodic laws of motion of a real mechanism imply the periodicity of all dynamic characteristics of the mechanism during such a movement, including the elastic displacements of its constituent links. This statement covers the most difficult problem of the dynamics of an elastically deformable body. However the existing publications devoted to the study of flexible mechanisms do not mention the periodicity of elastic displacements of the links when the mechanisms move according to periodic laws. This articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(16 reference statements)
0
0
0
Order By: Relevance
“…O(n). The application of this method has also been shown in the analysis of the oscillations of a double pendulum and slider-crank mechanism in the presence of elastic links in them [9]. Some studies of the oscillations of a double pendulum can also be found in [10,11].…”
Section: Introductionmentioning
confidence: 97%
“…O(n). The application of this method has also been shown in the analysis of the oscillations of a double pendulum and slider-crank mechanism in the presence of elastic links in them [9]. Some studies of the oscillations of a double pendulum can also be found in [10,11].…”
Section: Introductionmentioning
confidence: 97%